High-Capacity Compact Massive MIMO Array With Hybrid Decoupling Scheme - Li, Jinkai; Zhai, Huiqing; Zhao, Luyu; Chen, Teyan; Wang, Yani; Yang, Shuming; Xu, Wenwei (IEEE transactions on antennas and propagation, 2022)
The staggered placement of array antenna is a neoteric configuration to improve antenna isolation. On this basis, how to further effectively reduce the mutual couplings of different adjacent positions is a challenging subject. This article presents a novel decoupling strategy that integrated surrounding resonance net, array-antenna decoupling surface (ADS), and composite decoupling surface (CDS) that are introduced for ± 45^{\mathrm {^{° }}} dual-polarized, high-density, wideband base station applications. The proposed decoupling method is robust in reducing concurrently multicouplings occurring between various co-polarized antenna elements with the minimum spacing of only 0.3λ under staggered configuration. The results show that good co- polarized isolation of both the E- and H-plane orientations >25 dB over the 6-8 GHz can be attained. The good agreement between simulation and measurement proved that such a decoupling method can be suitable for base stations that have a stringent space constraint. Finally, the modified envelope correlation coefficient (ECC) and channel capacity of the proposed MIMO array are also studied, and the improvement of the communication quality by the proposed decoupling method is verified again.